MODERN LABORATORY DIAGNOSIS OF LIVER DISEASES (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
Liver diseases rank among the leading causes of chronic internal organ pathology and represent a serious medical and social problem. The effectiveness of treatment depends largely on timely and accurate diagnosis, which is why modern laboratory testing methods are of particular importance. Laboratory diagnostics enable the detection of pathological changes in the liver at an early stage and the assessment of the extent of damage.
Keywords: alanine aminotransferase (ALT), aspartate aminotransferase (AST), bilirubin, alkaline phosphatase, gamma-glutamyltransferase